Evaluation of Non-Invasive Markers to Show Fibrosis in Patients with Chronic Hepatitis B - Mahmut Çınar; Deniz İncaman; Mehmet Bayram; İskender Ekinci; Kader Irak; Ömür Tabak; Abdulbaki Kumbasar (GSAR PUBLISHERS, 2024)
Introduction: Liver biopsy is the gold standard in the evaluation of fibrosis in the treatment plan for hepatitis B, which is an important public health problem in the world and our country. There are disadvantages such as the development of complications in the biopsy procedure and the inability to represent the liver tissue. Therefore, non-invasive, objectively evaluated, and reproducible methods that can replace biopsy are being investigated. Material-Method: 201 patients aged 18 and over, who were diagnosed with chronic hepatitis B and applied to the internal medicine and gastroenterology outpatient clinics between January 2014 and December 2019, were included in the study. Results: When the diagnostic sensitivity of non-invasive markers according to the 7 tools of fibrosis was investigated in our study, it was seen that the best diagnostic test in the ≥F2 group was the King's score. Conclusion: Most of the non-invasive tests we evaluated can predict significant fibrosis with apparent accuracy, and with the help of non-invasive tests, the rate of unnecessary biopsies can be reduced.
Keywords: Hepatitis B virus, Fibrotic stage, Liver biopsy.; 3. Good health